Pengaruh Pengalaman Kerja, Tingkat Pendidikan, dan Pelatihan terhadap Pengembangan Karir Karyawan PT Telkom Indonesia Wilayah Brebes–Tegal–Slawi - Pramono, Pramono (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to analyze the influence of work experience, education level, and training on employee career development in PT Telkom Indonesia Brebes-Tegal-Slawi Region. The research method used was an associative quantitative approach with data collection through questionnaires to 150 randomly selected respondents. Data analysis was carried out using multiple linear regression to test the partial and simultaneous influence between variables. The results show that work experience, education level, and training have a positive and significant effect on career development both partially and simultaneously. A coefficient of determination value (R²) of 0.65 indicates that 65% of career development variations can be explained by these three variables. Among the three, training is the most dominant factor influencing employee career development. These findings confirm the importance of corporate investment in relevant training programs as well as support for improving employee education and work experience as a strategy to accelerate career development and improve organizational performance. In addition, the results of this research are expected to be a reference for management in designing sustainable human resource development policies that are adaptive to changes in the work environment.